PERILAKU SPIRITUAL DAN KEPUASAN KERJA KARYAWAN PERUSAHAAN PABRIK KELAPA SAWIT - Arrafiqur Rahman, Makmur (Jurnal Ilmiah Cano Ekonomos, 2015)
This study aimed to examine the effect of spiritual behavior on employee job satisfactionthrough the intervening variable of spiritual intelligence. By using quantitative research-surveydesign, sample was selected by purposive sampling technique as much as 108 people at one of thecompany employees of palm oil mill in Rokan Hulu. Primary data were obtained with the techniqueusing a Likert scale questionnaire and the data were analyzed with descriptive and path analysisapproach. The study concluded that spiritual behavior (X1) does not directly affect the jobsatisfaction of employees, but directly affects the spiritual intelegency employees (X2) and spiritualintelligenceemployees (X2) also directly affects employee’s job satisfaction palm oil mills. Thefindings suggested that management should facilitated formal learning and informal learnin,organizations also related understanding of spirituality, it is advisable also to strengthen employees'sense of security, well explained about the promotion, whether or not the employee has anopportunity to be promoted and be claritied of career, as well as the need for style situationalleadership, especially in explaining the perceive of employees’ fairness treatment.